The Impact of Perceived Social Support on Anxiety, Depression and Severity of Pain and Burnout Among Turkish Females With Fibromyalgia - Nermin GÜNDÜZ; Ahmet ÜŞEN; Emel AYDIN ATAR (Archives of Rheumatology, 2019)
Objectives: This study aims to assess the impact of perceived social support on burnout, severity of pain and comorbid anxiety and depression among Turkish females with fibromyalgia syndrome (FMS). Patients and methods: A total of 117 females including 65 patients with FMS (mean age 33.5±8.1 years; range 20 to 60 years) and 52 healthy controls (mean age 33.6±7.3 years; range 23 to 48 years) were included between January 2017 and May 2017. Following a semi-structured psychiatric interview by a psychiatrist, Sociodemographic Data Form, Mood and Anxiety Disorders Modules of Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders fourth edition Axis I Disorders (SCID-I), Hamilton Depression Rating Scale (HDRS), Hamilton Anxiety Rating Scale (HARS), Visual Analog Scale (VAS), Maslach Burnout Inventory (MBI) and Multidimensional Scale of Perceived Social Support (MSPSS) were applied to participants. Results: As a result of the semi-structured clinical interview conducted by a psychiatrist, the prevalence of any mood or anxiety disorder was found to be significantly more common in the FMS group. The proportion of patients diagnosed with any mood or anxiety disorder using SCID-I was significantly different among FMS (n=50, 76.92%) and healthy control (n=14, 33.33%) groups (p<0.001). Correlations between these variables were examined within the FMS group. There was a significant negative correlation between VAS and MSPSS. There were significant negative correlations between MSPSS and HDRS, HARS, all subscales of MBI. There were significant positive correlations between VAS and HDRS, HARS, all subscales of MBI. Conclusion: In conclusion, perceived social support was found to be strongly associated with depression, anxiety, burnout and severity of pain in patients with FMS. Our study provided support to emphasize the importance of perceived social support among females with FMS. Considering that FMS is associated with many physical and cognitive complaints in addition to pain, it can be considered as a multi-systemic disease requiring a multidisciplinary approach.